Raised dopamine metabolites in a case of malignant paraganglioma. Issue 776 (June 1990) - Florkowski, C. M.; Fairlamb, D. J.; Freeth, M. G.; Taylor, S. A.; Taylor, A.; Weinkove, C.; Jacobs, A. G.
Abstract : This paper describes the case of a malignant retroperitoneal paraganglioma with extensive metastases. The patient presented with a supraclavicular mass and an absence of hypertension. Exclusively raised dopamine metabolites were detected which may be a marker of a malignant process and account for the lack of hypertension.